Jalaluddin Rumi's Thoughts Regarding the Concept of Love as a Basis for Religious Moderation - Syah, Yoshy Hendra Hardiyan; Rosyad, Rifki (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2024)
This article examines Jalaluddin Rumi's thoughts on the concept of love as the basis for religious moderation. This article originates from a literature review or literature review to explain descriptively and discuss Jalaluddin Rumi's thoughts on the concept of love as the basis for religious moderation. In this article, the approach used is the Philosophical-Sufistic approach to the thoughts brought by Rumi, namely the concept of love. Jalaluddin Rumi answered and thoroughly discussed the concept of love as the basis for religious moderation in the book "Diwan As-Shams al-Din at-Thabrizi, Matsnawi, and Fihi Ma Fihi". The findings are that the existence of religious moderation is to encourage healthy religious practices, mutual understanding, mutual love, mutual respect and respect, and promote peace missions among all people, regardless of differences in their religious beliefs. Then related to Rumi's thoughts about love can be connected with the concept of religious moderation through four perspectives, namely unity of purpose and religion of love, tolerance and respect, unity with God, and love as self-transformation. Based on these four perspectives, Jalaluddin Rumi's overall thoughts about love offer a strong philosophical foundation for religious moderation. Then, if linked in the context of moderation, Rumi's thought teaches that it is important to view religion as a source of inspiration in life to achieve unity, peace, and respect among religious communities.